Hypertension care during the COVID‐19 pandemic in an integrated health care system. Issue 4 (14th March 2023) - Steiner, John F.; Powers, J. David; Malone, Allen; Lyons, Jason; Olson, Kari; Paolino, Andrea R.; Steiner, Claudia A.
Abstract: Retention in hypertension care, medication adherence, and blood pressure (BP) may have been affected by the COVID‐19 pandemic. In a retrospective cohort study of 64 766 individuals with treated hypertension from an integrated health care system, we compared hypertension care during the year pre‐COVID‐19 (March 2019–February 2020) and the first year of COVID‐19 (March 2020–February 2021). Retention in hypertension care was defined as receiving clinical BP measurements during COVID‐19. Medication adherence was measured using prescription refills. Clinical care was assessed by in‐person and virtual visits and changes in systolic and diastolic BP. The cohort had a mean age of 67.8 (12.2) years, 51.2% were women, and 73.5% were White. In 60 757 individuals with BP measurements pre‐COVID‐19, 16618 (27.4%) had no BP measurements during COVID‐19. Medication adherence declined from 86.0% to 80.8% ( p < .001). In‐person primary care visits decreased from 2.7 (2.7) to 1.4 (1.9) per year, while virtual contacts increased from 9.5 (12.2) to 11.2 (14.2) per year (both p < .001). Among individuals with BP measurements, mean (SD) systolic BP was 126.5 mm Hg (11.8) pre‐COVID‐19 and 127.3 mm Hg (12.6) during COVID‐19 ( p = .14). Mean diastolic BP was 73.5 mm Hg (8.5) pre‐COVID‐19 and 73.5 mm Hg (8.7) during COVID‐19 ( p = .77). Even in this integrated health care system, many individuals did not receive clinical BP monitoring during COVID‐19. Most individuals who remained in care maintained pre‐COVID BP. Targeted outreach may be necessary to restore care continuity and hypertension control at the population level.